2022
DOI: 10.1038/s41598-022-11547-4
|View full text |Cite
|
Sign up to set email alerts
|

Promoting a growth mindset decreases behavioral self-handicapping among students who are on the fixed side of the mindset continuum

Abstract: The present study examined the interplay between chronic intelligence beliefs, manipulated intelligence beliefs and self-handicapping processes. Prior studies showed that holding more of a fixed intelligence theory makes one vulnerable to resorting to self-protective mechanisms such as self-handicapping, while growth intelligence mindset can serve as a protective factor for self-handicapping. However, no prior studies have examined the potential interaction between pre-experimental intelligence beliefs, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…18 At present, many scholars claim that this theory is single-dimensional; that is, the way of thinking can change within a cognitive continuum, 19,20 so a fixed mindset is also called a low-growth mindset. 21 Research on growth mindset has produced many results in the field of learning and work, such as being beneficial to middle school students' learning engagement and academic literacy, 22,23 improving individual job satisfaction and achieving career success. 24,25 However, some scholars have argued that growth mindset can also help individuals develop healthy lifestyles, decrease bad living habits, predict individual mental health problems and increase happiness.…”
Section: Literature Review Growth Mindset and Meaning In Lifementioning
confidence: 99%
“…18 At present, many scholars claim that this theory is single-dimensional; that is, the way of thinking can change within a cognitive continuum, 19,20 so a fixed mindset is also called a low-growth mindset. 21 Research on growth mindset has produced many results in the field of learning and work, such as being beneficial to middle school students' learning engagement and academic literacy, 22,23 improving individual job satisfaction and achieving career success. 24,25 However, some scholars have argued that growth mindset can also help individuals develop healthy lifestyles, decrease bad living habits, predict individual mental health problems and increase happiness.…”
Section: Literature Review Growth Mindset and Meaning In Lifementioning
confidence: 99%
“…Hence, many studies have identified the factors and processes that lead to self-handicapping and its consequences (Núñez et al, 2021). Since self-handicapping is an avoidant behavior that leads to reduced performance and academic degradation, affects a person's personality and future adjustment, In recent years, academic self-handicapping has been proposed as a defect in self-regulation in the inability to control one's thoughts, emotions, feelings, and optimal performance by one's criteria (Khaneghahi et al, 2022;Török et al, 2022). Therefore, self-regulation is one of the essential variables in explaining the cause of self-handicapping.…”
Section: Self-handicappingmentioning
confidence: 99%
“…In recent years, academic self-handicapping has been proposed as a defect in self-regulation in the inability to control one’s thoughts, emotions, feelings, and optimal performance by one’s criteria ( Khaneghahi et al, 2022 ; Török et al, 2022 ). Therefore, self-regulation is one of the essential variables in explaining the cause of self-handicapping.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A fixed mindset perspective tends to weigh against these same ideas given its emphasis on the stability rather than the malleability of abilities. Indeed, as originally conceived, fixed and growth mindset exist as both ends of a continuum and therefore differ by degree rather kind (Dweck & Leggett, 1988;Dweck et al, 1995;Mercer & Ryan, 2010;Török et al, 2022;Yeager & Dweck, 2020). This is a characterization that has implications for appropriate approaches to measurement and thus one to which we return shortly.…”
mentioning
confidence: 92%